2019
DOI: 10.3390/dj7020040
|View full text |Cite
|
Sign up to set email alerts
|

Ratio between Height and Thickness of the Buccal Tissues: A Pilot Study on 32 Single Implants

Abstract: Background: Previous studies have suggested that mucosal height is related to the bone level and soft tissue thickness. The purpose of this pilot study was to investigate the ratio between the height and width of the tissues around single implants with a conical connection and platform switching. Methods: All patients receiving single implants (Anyridge®, MegaGen, Gyeongbuk, South Korea) and restored with single crowns, in a three-month period, were included in this study. After a provisionalization of 12 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 38 publications
(74 reference statements)
1
28
1
Order By: Relevance
“…In the present study, the buccal free gingival margin was found to mature coronally when the BBT was ≥1.5 mm (Group 2), as also described in a previous case report by Pereira et al [44]. Another study also reported that the buccal tissue thickness has a significant influence on its own height relative to the implant connection in order to maintain consistent proportions [10]. Hence, it is reasonable to conclude that increasing the buccal tissue thickness will induce increased tissue height and better stability over time.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In the present study, the buccal free gingival margin was found to mature coronally when the BBT was ≥1.5 mm (Group 2), as also described in a previous case report by Pereira et al [44]. Another study also reported that the buccal tissue thickness has a significant influence on its own height relative to the implant connection in order to maintain consistent proportions [10]. Hence, it is reasonable to conclude that increasing the buccal tissue thickness will induce increased tissue height and better stability over time.…”
Section: Discussionsupporting
confidence: 88%
“…Nowadays, aesthetic outcome plays a fundamental role in oral implantology [2]. Thus, current research has turned its attention to the parameters that determine the aesthetic success of rehabilitation [10]. Certainly, the height of the soft tissue around a dental implant is key in determining a natural aesthetic result [28], as no rehabilitation showing recessions can be considered an aesthetic achievement [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, fulfilling the aesthetic expectations of patients is one of the most challenging tasks in implant dentistry [1]. Factors that influence the aesthetic outcome of an implant-supported rehabilitation include, amongst others, the position of the implant [2], the quantity and quality of hard and soft tissues, and their adaptation over time [3].…”
Section: Introductionmentioning
confidence: 99%